Digitalisasi Pengelolaan Wakaf Produktif: Peluang dan Tantangan di Era Ekonomi Digital - Sani, Muhammad Anwar (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2025)
Digital transformation has had a profound impact on various aspects of life, including the management of productive waqf. This study aims to examine the potential and challenges of implementing digitalization in the management of productive waqf amid the growth of the digital economy. Using a qualitative approach through a literature review, this research analyzes academic studies, legal regulations, and technology-based waqf practices currently developing in Indonesia. The findings indicate that the adoption of digital technology offers significant opportunities to optimize productive waqf management by enhancing transparency, operational efficiency, and public participation through digital platforms such as crowdfunding, blockchain, and waqf management applications. Nevertheless, the digitalization process still faces several obstacles, including low digital literacy, insufficient regulatory support, as well as data security and public trust issues. Therefore, synergy between the government, nazhir institutions, and technology industry players is required to establish a modern, transparent, and sustainable productive waqf management system.